Elaboração, processamento e aceitação sensorial de hambuguer artesanal de frango - Araújo, Irving Matheus Medeiros de (Universidade Federal Rural do Semi-Árido, 2019)
The hamburger stands out as one of the most consumed delicacies, with acceptance in all social classes. However, in their manufacture, it is common to abuse artificial preservatives that increase shelf life, but which can lead to the development of serious diseases in the long run. In view of this, it is necessary to develop a handmade product that preserves the health of the consumer. Thus, this work had the objective of manufacturing four types of artisan chicken hamburger, with no preservatives, and a low cost of production, addressing a real problem, in which a company X presented difficulties in the production of chicken hamburgers. We tested some chicken hamburger recipes, which went through two stages of sensory analysis. In the first, only homemade hamburgers were compared. In the second, the three best samples evaluated to be confronted with an industrialized hamburger were chosen, in order to verify the final acceptance of the participants in the attributes as color, flavor, aroma, consistency and texture applied to different age groups. With the results obtained, it was possible to reach a conclusion in which the sample 3 had the most prominence, respectively, in the first and second sensorial analysis. In addition, it opens up the opportunity for market increase for company X who will be able to process and market a new product in its dependencies, as well as, provide for their franchises.
Artigo
Keywords: Hambúrgueres; Frango; Análise sensorial; Produtos artesanais; Hamburgers; Chicken; Sensory analysis; Handmade products; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA